Molecular dynamics simulation and binding free energy studies of novel leads belonging to the benzofuran class inhibitors of Mycobacterium tuberculosis Polyketide Synthase 13 - Cruz, Jorddy N; Costa, José F S; Khayat, André S; Kuca, Kamil; Barros, Carlos A L; Neto, A M J C (Journal of biomolecular structure & dynamics, 2019)
In this work, the binding mechanism of new Polyketide Synthase 13 (Pks13) inhibitors has been studied through molecular dynamics simulation and free energy calculations. The drug Tam1 and its analogs, belonging to the benzofuran class, were submitted to 100 ns simulations, and according to the results obtained for root mean square deviation, all the simulations converged from approximately 30 ns. For the analysis of backbone flotation, the root mean square fluctuations were plotted for the Cα atoms; analysis revealed that the greatest fluctuation occurred in the residues that are part of the protein lid domain. The binding free energy value (ΔGbind) obtained for the Tam16 lead molecule was of -51.43 kcal/mol. When comparing this result with the ΔGbind values for the remaining analogs, the drug Tam16 was found to be the highest ranked: this result is in agreement with the experimental results obtained by Aggarwal and collaborators, where it was verified that the IC50 for Tam16 is the smallest necessary to inhibit the Pks13 (IC50 = 0.19 μM). The energy decomposition analysis suggested that the residues which most interact with inhibitors are: Ser1636, Tyr1637, Asn1640, Ala1667, Phe1670, and Tyr1674, from which the greatest energy contribution to Phe1670 was particularly notable. For the lead molecule Tam16, a hydrogen bond with the hydroxyl of the phenol not observed in the other analogs induced a more stable molecular structure. Aggarwal and colleagues reported this hydrogen bonding as being responsible for the stability of the molecule, optimizing its physic-chemical, toxicological, and pharmacokinetic properties.
Keywords: vodíková vazba; antituberkulotika; simulace molekulového dockingu; Structure-Activity Relationship; vztahy mezi strukturou a aktivitou; Polyketide Synthases; Protein Binding; Protein Conformation; Molecular Docking Simulation; polyketidsynthasy; vazebná místa; Binding Sites; molekulární struktura; bakteriální proteiny; aminokyseliny; Amino Acids; Benzofurans; Molecular Structure; simulace molekulární dynamiky; objevování léků; Antitubercular Agents; Molecular Dynamics Simulation; benzofurany; vazba proteinů; Hydrogen Bonding; Bacterial Proteins; Drug Discovery; konformace proteinů